Neuropathic cancer pain: prevalence, pathophysiology, and management - Yoon, So Young (Korean J Intern Med, 2018)
Neuropathic cancer pain (NCP) is caused by nerve damage attributable to the cancer per se, and/or treatments including chemotherapy, radiotherapy, and surgery; the prevalence is reported to be as high as 40%. The etiologies of NCP include direct nerve invasion or nerve compression by the cancer, neural toxicity, chemotherapy, and radiotherapy. NCP is subdivided into plexopathy, radiculopathy, and peripheral neuropathies, among several other categories. The clinical characteristics of NCP differ from those of nociceptive pain in terms of both the hypersensitivity symptoms (burning, tingling, and an electrical sensation) and the hyposensitivity symptoms (numbness and muscle weakness). Recovery requires several months to years, even after recovery from injury. Management is complex; NCP does not usually respond to opioids, although treatments may feature both opioids and adjuvant drugs including antidepressants, anticonvulsants, and anti-arrhythmic agents, all of which improve the quality-of-life. This review addresses the pathophysiology, clinical characteristics and management of NCP, and factors rendering pain control difficult.